Agronomic and Environmental Assessment of a Polyculture Rooftop Soilless Urban Home Garden in a Mediterranean City - Boneta, Anna; Rufí-Salís, Martí; Ercilla-Montserrat, Mireia; Gabarrell, Xavier; Rieradevall, Joan (Frontiers in Plant Science, 2019)
Urban planning has been focusing its attention on urban rooftop agriculture as an innovative way to produce local and reliable food in unused spaces in cities. However, there is a lack of quantitative data on soilless urban home gardens and their contribution to self-sufficiency. The aim of the present study is to provide quantitative agronomic and environmental data on an actual soilless urban garden to estimate its degree of self-sufficiency and sustainability. For this purpose, an 18 m2 soilless polyculture rooftop urban home garden in the city center of Barcelona was analyzed. From 2015 to 2017, 22 different crops were grown to feed 2 people in an open-air soilless system, and a life cycle assessment was performed. A total productivity of 10.6 kg/m2/year was achieved, meaning that 5.3 m2 would be needed to fulfil the yearly vegetable requirements of an average citizen (in terms of weight). Considering the vegetable market basket of Catalonia, an 8.2 m2 soilless garden would be needed to cover 62% of the market basket for one person. The top 5 most productive crops were tomato, chard, lettuce, pepper and eggplant, accounting for 85.5% of the total production. The water consumption was 3.7 L/m2/day, and 3.3 kg/year/m2 of waste was generated. A high degree of self-sufficiency was achieved, although adjustments could be made to adapt the production to the market basket. The environmental assessment showed that the fertilizers and their associated leachates accounted for the highest environmental impacts in all the studied impact categories. Overall, 0.6 kg CO2 eq. was generated per kg of vegetables produced. The quantitative data provided by the present study offer a reference from which urban planners and researchers can project future implementations of rooftop urban agriculture UA on a large scale.